Supported Rh2O3 sub-nanometer size particles for the direct amination of ethylene with piperidine. Issue 10 (14th April 2022) - Sengupta, Manideepa; Khan, Tuhin Suvra; Das, Subhasis; Singh, Gurmeet; Kumar, Ravi; Bhattacharya, Dibyendu; Haider, M. Ali; Islam, Sk Manirul; Bordoloi, Ankur
Abstract : The π-binding mode of Rh80 O120 rather than a stronger σ-binding mode of Rh2 O3 (100) surface to CC, reflects the superior catalytic activity of Rh2 O3 sub-nanoparticles confined in SiO2 towards ethylenic hydroamination, in contrast to large particle. Abstract : Designing controlled nanostructured catalysts is always a demanding approach for bridging the gap between homogeneous and heterogeneous catalysis. In this report, 0.8–1 nm size Rh2 O3 nanoparticles confined in silica meso-channels have been prepared through a facile template-assisted synthesis approach. The supported Rh2 O3 particles presented excellent activity (TON = 543) towards the challenging direct addition of piperidine to ethylene under low pressure, with >99% selectivity towards the desired N -ethyl piperidine. The superior catalytic activity of the nanoclusters over large particles was predicted using the density functional theory and could be attributed to the binding mode of ethylene with the Rh species, wherein a weaker π-binding mode rather than the stronger σ-mode of binding of ethylene with the Rh species facilitates the C–N coupling reaction step.